Biases in facial and vocal emotion recognition in chronic schizophrenia - Dondaine, Thibaut; Robert, Gabriel; Péron, Julie; Grandjean, Didier; Vérin, Marc; Drapier, Dominique; Millet, Bruno (Frontiers in Psychology, 2014)
There has been extensive research on impaired emotion recognition in schizophrenia in the facial and vocal modalities. The literature points to biases toward non-relevant emotions for emotional faces but few studies have examined biases in emotional recognition across different modalities (facial and vocal). In order to test emotion recognition biases, we exposed 23 patients with stabilized chronic schizophrenia and 23 healthy controls to emotional facial and vocal tasks asking them to rate emotional intensity on visual analog scales. Results showed that patients performed poorer than healthy controls whatever the task. However, we showed that patients with schizophrenia provided higher intensity ratings on the nontarget scales (e.g. surprise scale for fear stimuli) than healthy controls for the both tasks. Furthermore, with the exception of neutral vocal stimuli, they provided the same intensity ratings on the target scales as the healthy controls. These findings suggest that patients with chronic schizophrenia have emotional biases when judging emotional stimuli in the visual and vocal modalities. These biases may stem from a basic sensorial deficit, a high-order cognitive dysfunction, or both. The respective roles of prefrontal-subcortical circuitry and the basal ganglia are discussed.